2017
DOI: 10.1002/erv.2546
|View full text |Cite
|
Sign up to set email alerts
|

Psychophysiological Changes during Pure vs Guided Mirror Exposure Therapies in Women with High Body Dissatisfaction: What Are They Learning about Their Bodies?

Abstract: This study aimed to examine the psychophysiological changes resulting from two mirror exposure treatments that are effective at reducing body dissatisfaction. Thirty-five university women with body dissatisfaction and subclinical eating disorders were randomly assigned to one of two groups: pure (n = 17) or guided exposure (n = 18). The participants received six sessions of treatment. Their thoughts, feelings and avoidance behaviours were assessed after each session. Their subjective discomfort, heart rate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 28 publications
2
22
0
Order By: Relevance
“…In the same line, Trentowska et al [ 48 ] found a cognitive and emotional (although not physiological) habituation within and between ME sessions in patients with ED. Nevertheless, Díaz-Ferrer et al [ 9 ] found that the subjective discomfort was maintained in the first session without evidence of within-session habituation process, making it comparable to the inhibitory learning model of extinction [ 51 , 52 ]. Hence, it is important to test whether the adoption of an expansive posture has negative consequences for the therapy, impeding the necessary negative response claimed by some models (e.g., [ 50 ]), or, in contrast, it has positive consequences for the therapy through the increase in positive emotions, making within-session habituation easier (e.g., increasing the view of one’s ability to actively cope with the exposure), making between-session habituation easier (e.g., increasing the adherence to several sessions of exposure therapy), or making easier the development of new non-threating associations within sessions, competing with the original negative response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same line, Trentowska et al [ 48 ] found a cognitive and emotional (although not physiological) habituation within and between ME sessions in patients with ED. Nevertheless, Díaz-Ferrer et al [ 9 ] found that the subjective discomfort was maintained in the first session without evidence of within-session habituation process, making it comparable to the inhibitory learning model of extinction [ 51 , 52 ]. Hence, it is important to test whether the adoption of an expansive posture has negative consequences for the therapy, impeding the necessary negative response claimed by some models (e.g., [ 50 ]), or, in contrast, it has positive consequences for the therapy through the increase in positive emotions, making within-session habituation easier (e.g., increasing the view of one’s ability to actively cope with the exposure), making between-session habituation easier (e.g., increasing the adherence to several sessions of exposure therapy), or making easier the development of new non-threating associations within sessions, competing with the original negative response.…”
Section: Discussionmentioning
confidence: 99%
“…It generally consists of observing and describing each part of the person’s own body in a full-length mirror for a long period of time while wearing tight fitting clothes [ 5 ]. ME has been shown to be effective in improving several important outcomes (e.g., dissatisfaction, negative body-related emotions and cognitions, or other aspects of ED psychopathology) in clinical samples with ED (e.g., [ 6 8 ]), as well as in non-clinical samples (e.g., [ 9 , 10 ]).…”
Section: Introductionmentioning
confidence: 99%
“…15 Diaz-Ferrer et al described how conflicts with self-image may promote EDs; however, mirror exposure therapy may improve self-image. 16 Mirrors may be a positive teaching tool in dance environments but only when contextualised appropriately.…”
Section: Dance and Healthmentioning
confidence: 99%
“…In pure mirror exposure, subjects simply view their whole bodies with or without commenting on the elicited emotions and cognitions, without any further directions from the experimenter or therapist. In contrast, in guided mirror exposure, subjects are directed to focus on specific parts of their bodies and can be asked to describe the emerging thoughts and feelings in a more controlled manner (Moreno-Domínguez et al, 2012;Díaz-Ferrer et al, 2017). As a research tool, mirror exposure has been used to study not only the quality and regulation of emotional responses to one's own body (Vocks et al, 2007;Trentowska et al, 2013;Servián-Franco et al, 2015), but also the long-term process of body acceptance or normalization of body image resulting from repeated body exposure (Key et al, 2002;Delinsky and Wilson, 2006;Trentowska et al, 2014).…”
Section: Introductionmentioning
confidence: 99%